GROWTH AND CAROTENE SYNTHESIS BY THE STRAINS BACILLUS AMYLOLIQUEFACIENS UCM B-5113 AND B. SUBTILIS 1.1 AT SUBMERGED CULTIVATION - О. О. Нечипуренко; М. А. Хархота; К. С. Бордунос; Л. В. Авдєєва (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2015)
Aim. The aim was to study the dynamics of the growth and carotene synthesis by the strains B. amyloliquefaciens UCM B-5113 and Bacillus 1.1 at submerged cultivation. Methods. Bacteria were cultured on synthetic medium and medium with molasses in periodic conditions. The amount of absolutely dry bacterial mass (g/l), the total content of carotenoids (mg/l) were determined spectrophotometrically at a wavelength of 540 and 440 nm, respectively. The pigments extraction was carried out with the use of mixture of chloroform and methanol (2:1). Results. The maximum bacterial cells concentration of the strains B. subtilis 1.1 B. amyloliquefaciens UCM B-5113 after cultivation on medium with molasses were 3.6 ± 0.2 ×1010 and 4.5 ± 0.3 × 1010 CFU/ml, respectively, and 10 times higher than the values obtained in the synthetic medium. Biomass yield of the strain B. subtilis 1.1 on complex medium was 4.5 g/l, and on synthetic –1.7 g/l; the data for B. amyloliquefaciens UCM B-5113 – 5.0 g/l and 2 g/l, respectively. Total carotenoid content of the strain B. subtilis 1.1 on complex medium was 965 mg/l of completely dry biomass (CDB), on the synthetic – 197 mg/l; the data for the strain B. amyloliquefaciens UCM B-5113 – 1356 mg/l and 173 mg/l, respectively. Conclusion. The complex medium with molasses needs to be used to obtain a high amount of bacterial biomass and carotenoid pigments of investigated strains. The quantity of viable cells of the strains B. subtilis 1.1 and B. amyloliquefaciens UCM B-5113 after cultivation on medium with molasses was 10 times higher than on synthetic, the maximum biomass – 3 and 2.5 times higher, the total carotenoid content – 5 and 8 times higher, respectively.